(untitled) (Praxis Educativa, 2024)
This text raises a series of reflections on how problematic it would be to assume the discourses that seek to outline the current educational system, without sufficient reflection on the conception of the school, the role of the teacher and the territory in the training processes. This is how three parts are structured, in the first, the implications of thinking about the role of the school from emerging paradigms, current demands and its historical role in society are exposed. In the second part, a series of aspects are exposed around the link between reflection and pedagogical practice. To, finally, put on the table the role of the territory in the training processes and how, from the geopedagogy approach, a relevant and valid field can be found from which to think about training and education today.